Targeting CCR5 as a Component of an HIV-1 Therapeutic Strategy - Mohamed, Hager; Gurrola, Theodore; Berman, Rachel; Collins, Mackenzie; Sariyer, Ilker K.; Nonnemacher, Michael R.; Wigdahl, Brian (Frontiers in Immunology, 2022)
Globally, human immunodeficiency virus type 1 (HIV-1) infection is a major health burden for which successful therapeutic options are still being investigated. Challenges facing current drugs that are part of the established life-long antiretroviral therapy (ART) include toxicity, development of drug resistant HIV-1 strains, the cost of treatment, and the inability to eradicate the provirus from infected cells. For these reasons, novel anti-HIV-1 therapeutics that can prevent or eliminate disease progression including the onset of the acquired immunodeficiency syndrome (AIDS) are needed. While development of HIV-1 vaccination has also been challenging, recent advancements demonstrate that infection of HIV-1-susceptible cells can be prevented in individuals living with HIV-1, by targeting C-C chemokine receptor type 5 (CCR5). CCR5 serves many functions in the human immune response and is a co-receptor utilized by HIV-1 for entry into immune cells. Therapeutics targeting CCR5 generally involve gene editing techniques including CRISPR, CCR5 blockade using antibodies or antagonists, or combinations of both. Here we review the efficacy of these approaches and discuss the potential of their use in the clinic as novel ART-independent therapies for HIV-1 infection.